Fault analysis and maintenance of high voltage transmission line. Issue 4 (May 2021) - Yi, Ren
Abstract: In recent years, with the continuous expansion of power transmission scale, high voltage transmission lines also began to appear. We can see that high-voltage transmission lines provide security for social development, at the same time, we can not ignore its later maintenance and management work. In the operation process of high-voltage transmission line, it will be affected by various factors and prone to failure, which will bring a certain impact on people's life and production, and even directly threaten human life safety, health and property safety. High voltage transmission is a highly technical work, which is special in itself. If the technology can not keep up or the supervision is weak, it may lead to safety problems. External environmental factors will also significantly interfere with high voltage transmission. Therefore, it will focus on the analysis of high voltage transmission factors, operation characteristics and maintenance measures.